The Evolution of an Innovation Capability: Making Internal Idea Competitions Work in a Large EnterpriseOne firm evolved its idea competitions into a broad innovation management system. Issue 2 (4th March 2017) - Smith, Calvin; Fixson, Sebastian K.; Paniagua-Ferrari, Carlos; Parise, Salvatore
OVERVIEW: As a form of crowdsourcing, idea competitions offer a mechanism to engage larger groups in innovation activities. While much of the literature on crowdsourcing focuses on idea competitions that cross a firm's boundaries to engage external partners, relatively little is known about how this approach can be used within large companies to engage the internal community. We describe how an internal idea competition in a large company has evolved over time into a much broader innovation management system that supports a range of different types of innovations, and how it has altered the firm's overall approach to innovation and corporate entrepreneurship.